Evaluation of microbial risk factors in prepared homemade food in Al-Zawia City, Libya. - Elzawi, Amina K.; Bshena, .Nadia E. (Libyan Journal of Science &Technology, 2025)
Foodborne infections remain a public health issue, emphasizing the need to understand microbiological dangers in home food preparation. This study analyzes foodborne pathogen parameters to assess home cooking microbiological risks. A questionnaire-based cross-sectional study examined microbial 1 in home food preparation. The questionnaire gathers data providing a comprehensive understanding of microbiological risk factors. Using IBM SPSS Statistics, statistical analysis will reveal variable linkages. The study reveals profound links in home food preparation. Participants with lower levels of education have a notable correlation with increased presence of pathogens history (p=0.00638*). Significantly, 22.85% of individuals indicate a previous occurrence of foodborne infections, with Salmonella spp. (12.85%), E. coli (7.15%), and Campylobacter spp. (2.85%) being the most commonly observed. There are strong associations between hygienic practices: hand washing (p = 0.00014*), surface cleaning (p = 0.00066*), and thermometer use (p=0.00008*). Preservation behaviors exhibit notable correlations: checking expiry dates (p=0.000235*), promptly refrigerating (p<0.00001*), and defrosting techniques (p=0.04882*). There is a significant correlation between education (p=0.00638*) and awareness (p=0.00129*) concerning pathogen history. Diverse sources of information indicate a non-significant association (p=0.8878). This study emphasizes the need for focused food safety measures including education and awareness to improve home food safety. Understanding these linkages allows people to adopt safer cooking practices, improving health and safety. The public health effects require awareness of home food preparation procedures to prevent microbiological risks.